Mental Health Service Provision in Low- and Middle-Income Countries. (24th March 2017) - Rathod, Shanaya; Pinninti, Narsimha; Irfan, Muhammed; Gorczynski, Paul; Rathod, Pranay; Gega, Lina; Naeem, Farooq
This article discusses the provision of mental health services in low- and middle-income countries (LMICs) with a view to understanding the cultural dynamics–how the challenges they pose can be addressed and the opportunities harnessed in specific cultural contexts. The article highlights the need for prioritisation of mental health services by incorporating local population and cultural needs. This can be achieved only through political will and strengthened legislation, improved resource allocation and strategic organisation, integrated packages of care underpinned by professional communication and training, and involvement of patients, informal carers, and the wider community in a therapeutic capacity.